The Metabolic Responses to Aerial Diffusion of Essential Oils - Wu, Yani; Zhang, Yinan; Xie, Guoxiang; Zhao, Aihua; Pan, Xiaolan; Chen, Tianlu; Hu, Yixue; Liu, Yumin; Cheng, Yu; Chi, Yi; Yao, Lei; Jia, Wei (PLOS ONE, 2012)
Anxiety disorders are the most prevalent psychiatric disorders and affect a great number of people worldwide. Essential oils, take effects through inhalation or topical application, are believed to enhance physical, emotional, and spiritual well-being. Although clinical studies suggest that the use of essential oils may have therapeutic potential, evidence for the efficacy of essential oils in treating medical conditions remains poor, with a particular lack of studies employing rigorous analytical methods that capture its identifiable impact on human biology. Here, we report a comprehensive gas chromatography time-of-flight mass spectrometry (GC-TOFMS) based metabonomics study that reveals the aromas-induced metabolic changes and the anxiolytic effect of aromas in elevated plus maze (EPM) induced anxiety model rats. The significant alteration of metabolites in the EPM group was attenuated by aromas treatment, concurrent with the behavioral improvement with significantly increased open arms time and open arms entries. Brain tissue and urinary metabonomic analysis identified a number of altered metabolites in response to aromas intervention. These metabolic changes included the increased carbohydrates and lowered levels of neurotransmitters (tryptophan, serine, glycine, aspartate, tyrosine, cysteine, phenylalanine, hypotaurine, histidine, and asparagine), amino acids, and fatty acids in the brain. Elevated aspartate, carbohydrates (sucrose, maltose, fructose, and glucose), nucleosides and organic acids such as lactate and pyruvate were also observed in the urine. The EPM induced metabolic differences observed in urine or brain tissue was significantly reduced after 10 days of aroma inhalation, as noted with the loss of statistical significance on many of the metabolites in the aroma-EPM group. This study demonstrates, for the first time, that the metabonomics approach can capture the subtle metabolic changes resulting from exposure to essential oils and provide the basis for pinpointing affected pathways in anxiety-related behavior, which will lead to an improved mechanistic understanding of anxiolytic effect of essential oils.